Build pairwise correlation and regression analysis skills and create econometric models. (Eurasian Scientific Herald, 2024)
In this article, the author presents a step-by-step process of creating and analyzing double-factor econometric models. In creating econometric models, students were first divided into groups and given tasks. In this way, students will develop the skills of calculating the correlation coefficient and analyzing the relationship between factors. A system of normal equations was formed to create a regression equation using the "method of least squares". Skills for performing econometric analysis based on the created model are also provided